Eye Movement Sequences during Simple versus Complex Information Processing of Scenes in Autism Spectrum Disorder. (19th July 2011) - Au-Yeung, Sheena K.; Benson, Valerie; Castelhano, Monica; Rayner, Keith
Abstract : Minshew and Goldstein (1998) postulated that autism spectrum disorder (ASD) is a disorder of complex information processing. The current study was designed to investigate this hypothesis. Participants with and without ASD completed two scene perception tasks: a simple "spot the difference" task, where they had to say which one of a pair of pictures had a detail missing, and a complex "which one's weird" task, where they had to decide which one of a pair of pictures looks "weird". Participants with ASD did not differ from TD participants in their ability to accurately identify the target picture in both tasks. However, analysis of the eye movement sequences showed that participants with ASD viewed scenes differently from normal controls exclusively for the complex task. This difference in eye movement patterns, and the method used to examine different patterns, adds to the knowledge base regarding eye movements and ASD. Our results are in accordance with Minshew and Goldstein's theory that complex, but not simple, information processing is impaired in ASD.